1870 Ga. Laws 421, title XVI, no. 285, § 1 - (:unkn) unknown (General Publisher, 1870)
Prohibiting carrying “any dirk, bowie-knife, pistol or revolver, or any kind of deadly weapon, to any court of justice, or any election ground or precinct, or any place of public worship, or any other public gathering in this State, except militia muster-grounds."
--
Keywords: CARRY - CERTAIN PUBLIC PLACES